Regulation of pore cell structures of coal-based carbon foams based on the nucleation mechanism of microcellular polymer. Issue 10 (July 2018) - Xu, Guozhong; Gao, Ruiyuan; Jin, Wenwu; Zou, Jizhao; Xiong, Xinbai; Li, Xiaohua; Zeng, Xierong
Abstract: It is widely accepted that the performance of carbon foams can be regulated by the tailoring of pore cell structures to meet the requirements of various applications. However, no theory has been used to date for guiding such regulation. In this work, carbon foams were prepared by saturating vitrinite concentrate with nitrogen gas under high pressure. The influence of key factors on the pore cell structure of carbon foams was investigated systematically. The results showed that the mean cell diameter and the bulk density of carbon foams can be regulated, respectively, in the ranges 140–440 µm and 0.29–0.75 g/cm 3, which indicates that vitrinite concentrate separated from fat coal is highly suitable for the preparation of carbon foams. The variation trends of the pore cell structures were well explained by combining the homogeneous nucleation mechanism of microcellular polymer with the viscosity of the fusant formed from vitrinite concentrate. The inherent reason for all the variation trends is related to the gas nuclei density and viscosity of the fusant. More importantly, a strategy is suggested to successfully accomplish the design and regulation of the pore structure of carbon foams by taking into account the homogeneous nucleation mechanism and viscosity of the fusant.